Furan Measurement in Transformer Oil by UV-Vis Spectral Response Using Fuzzy Logic - Lai, Sin; Abu-Siada, Ahmed; Islam, Syed (Department of Electrical and Electronic Engineering (EEE), Bangladesh University of Engineering and Technology, 2008)
Furan derivatives (2-acetyl furan, 2-furfural, 5-methyl-2-furfural, 5-hydroxymethyl 2-furfural, and 2-furfurylalcohol) presence in transformer oil are the key indicators of the solid dielectric degradation. In recent technology, such deterioration is measured according to ASTM D 5837 standard. However, the method requires very expensive and sophisticated equipment like High-Performance Liquid Chromatography (HPLC) or Gas Chromatography-Mass Spectrometry (GC/MS). This paper proposes a low cost and convenient approach in furan contents estimation based on UV-Vis spectrometry and Fuzzy Logic Theory.